2019
DOI: 10.1021/acs.jpclett.9b00838
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent Colloidal Nanohelices Self-Assembled from CdSe Magic-Size Clusters via Nanoplatelets

Abstract: Reports on photoluminescent colloidal semiconductor two-dimensional (2D) helical nanostructures with one-dimensional quantum confinement are relatively rare. Here, we discuss the formation of such photoluminescent nanostructures for CdSe. We show that when as-synthesized unpurified zero-dimensional (0D) CdSe magic-size clusters (MSCs) (passivated by carboxylate ligands with three-dimensional quantum confinement) are dispersed in a solvent (such as toluene or chloroform) containing hexadecylamine and then subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…The magic‐sized CdSe and its related nanoclusters have been identified to be metastable precursor clusters that have been implicated in nanocrystal nucleation, transforming into various colloidal nanocrystals, such as quantum wires, nanosheets, nanorods, nanoribbons, nanohelices, nanodisks, and nanoplatelets. [ 16,62,102–106 ] Hyeon et al. [ 13 ] proposed the initial formation of a metal‐salt primary‐amine bilayer 2D template followed by lamellar structures as the predominant path for the CdSe nanosheet synthesis.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…The magic‐sized CdSe and its related nanoclusters have been identified to be metastable precursor clusters that have been implicated in nanocrystal nucleation, transforming into various colloidal nanocrystals, such as quantum wires, nanosheets, nanorods, nanoribbons, nanohelices, nanodisks, and nanoplatelets. [ 16,62,102–106 ] Hyeon et al. [ 13 ] proposed the initial formation of a metal‐salt primary‐amine bilayer 2D template followed by lamellar structures as the predominant path for the CdSe nanosheet synthesis.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…Similarly, very small Stokes shift can be found in atom-scale-uniform magic sized quantum dots or 2D quantum materials with magic thickness. [61,62] The spectra of CsPbBr 3 nanorods also can be tuned by the halide ion exchange, with the nanorod morphology retained. The ion exchange prepared CsPbCl x Br 3-x and CsPbBr x I 3-x nanorods have decreased and increased diameters compared with the starting CsPbBr 3 nanorods, respectively, consistent with the crystal lattice change (Figures S1 and S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, very small Stokes shift can be found in atom‐scale‐uniform magic sized quantum dots or 2D quantum materials with magic thickness. [ 61,62 ]…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the obtained mass spectra exhibited more peaks than the spectra obtained for CdSe and ZnSe, which had only one prominent peak. 171,172 Single singularity in the resulting cluster was also observed as different sized cluster contribution was not present. It was also interpreted that these alloy clusters were formed by integrating zinc atoms instead of similar cadmium atoms or vice-versa.…”
Section: Doping Of Cdse Msncsmentioning
confidence: 92%
“…Energy transfer from host band state of semiconductor to states of Mn 2+ was confirmed on the basis of photoluminescence emission (PLE) spectrum, making it obvious that the manganese ions were present in a Cd 2+ site. 171 Laser desorption/ionization time-of-flight mass spectroscopy was employed for characterizing the prepared clusters. It was observed that the obtained mass spectra exhibited more peaks than the spectra obtained for CdSe and ZnSe, which had only one prominent peak.…”
Section: Doping Of Cdse Msncsmentioning
confidence: 99%